Literature Study: Mandatory Contribution of Land and Building Rights Acquisition Duty (BPHTB) - Ayuningtyas, Eka; Muna, Naily El (INCOME: Innovation of Economics and Management, 2024)
Mandatory BPHTB contributions are local original revenues that must be paid by the payer to the local government that is useful for development. In this writing, we will discuss various information related to BPHTB mandatory contributions with the literature study method. In this literature study, there is information on previous research that provides answers on the legal basis of the mandatory contribution of the Mandatory Acquisition Duty on Land and Building Rights, the subject and object of the mandatory contribution of the BPHTB and the amount of the tariff and how to calculate the mandatory contribution of the BPHTB. Based on the results of this literature, it can be concluded that the mandatory BPHTB contribution has a strong and clear legal basis, the subject and object of the mandatory contribution include individuals and legal entities of BPHTB and the amount of the tariff and how to calculate the mandatory contribution of the BPHTB Mandatory Contribution, while the tariff in the payment of the Land and Building Rights Acquisition Duty (BPHTB) and the amount of the tariff and the method of calculating the mandatory contribution of the Mandatory Land and Building Rights Acquisition Fee (BPHTB) is 5%.